Overexpression of the Wheat (Triticum aestivum L.) TaPEPKR2 Gene Enhances Heat and Dehydration Tolerance in Both Wheat and Arabidopsis - Zang, Xinshan; Geng, Xiaoli; He, Kexiang; Wang, Fei; Tian, Xuejun; Xin, Mingming; Yao, Yingyin; Hu, Zhaorong; Ni, Zhongfu; Sun, Qixin; Peng, Huiru (Frontiers in Plant Science, 2018)
The yield of wheat (Triticum aestivum L.) is adversely affected by heat and drought stresses in many regions of the world. A PEP carboxylase kinase-related kinase gene, TaPEPKR2, was identified from our previous transcriptome analysis of a heat-tolerant wheat cultivar (TAM107). Based on the wheat cultivar Chinese Spring (CS) genome sequence, TaPEPKR2 was mapped to chromosome 5B. Expression pattern analysis revealed that TaPEPKR2 was induced by heat and polyethylene glycol (PEG). To confirm the function of TaPEPKR2 in wheat, TaPEPKR2 was transformed into the wheat cultivar Liaochun10 (LC10), and the transgenic plants exhibited enhanced heat and drought stress tolerance. To examine whether TaPEPKR2 exhibit the same function in dicotyledonous Arabidopsis, TaPEPKR2 was transformed into Arabidopsis, and overexpression of TaPEPKR2 functionally also enhances tolerance to heat and drought stresses. Our results suggest that TaPEPKR2 plays an important role in heat and drought stress tolerance, and could be utilized in transgenic breeding of wheat and other crop plants.